The Influence of Transformational Leadership and Employee Engagement to Organizational Citizenship Behavior (OCB) and the Effect to Division Effectiveness at PT. X in Indonesia - S. Marinda, Vina; Haizam Mohd Saudi, Mohd; Maya Dora, Yenny; Surayya Mohd Saudi, Nur (International Journal of Engineering and Technology, 2018)
Division effectiveness can be achieved and grown by a good OCB, which such behavior will grow both through the influence of good employee engagement and transformational leadership. The purposes of this research are to figure out how transformational leadership, employee engagement, OCB, and division effectiveness in PT. X and to figure out how influence of transformational leadership and employee engagement on OCB and their impact on division effectiveness in PT. X either simultaneously or partially. Descriptive research method is used to get an idea of transformational leadership, employee engagement, OCB, and division effectiveness quality. Verificative research method tests truth through collecting data in the field and tests causal hypotheses about influence of two independence variables (transformational leadership and employee engagement), one intervening variable OCB and one dependence variable (division effectiveness) by using path analysis. The paper is shows that transformational leadership and employee engagement has significant influence to OCB and also affect division effectiveness either simultaneous or partial.Â Â